2017
DOI: 10.3399/bjgp17x689413
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of topical betamethasone to treat chronic chilblains: a randomised clinical trial in primary care

Abstract: BackgroundGPs prescribe topical corticosteroids to patients with chronic chilblains despite poor evidence for their effectiveness. The authors of the current study therefore decided to assess the effectiveness of topical steroids in a primary care setting.AimTo assess the effectiveness of topical application of betamethasone valerate 0.1% cream in patients with chronic chilblains.Design and settingA placebo-controlled, double-blind, crossover, randomised clinical trial in a Dutch primary care setting.MethodThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
9
0
6
Order By: Relevance
“…Although often used, the effect of topical betamethasone remains controversial. In a randomized trial of 34 patients (betamethasone valerate 0.1 % twice daily) for six weeks compared with placebo, there was no significant difference in symptoms between the two groups [60]. In their literature review, the Mayo Clinic shows a benefit of topical corticosteroid in 6 out of 8 patients [4].…”
Section: Managementmentioning
confidence: 98%
“…Although often used, the effect of topical betamethasone remains controversial. In a randomized trial of 34 patients (betamethasone valerate 0.1 % twice daily) for six weeks compared with placebo, there was no significant difference in symptoms between the two groups [60]. In their literature review, the Mayo Clinic shows a benefit of topical corticosteroid in 6 out of 8 patients [4].…”
Section: Managementmentioning
confidence: 98%
“…18 In March 2017, Souwer et al assessed the efficacy of twice daily application of topical betamethasone valerate 0.1% cream for 6 weeks to treat chilblains, but no clinically or statistically significant differences were found when compared to the placebo. 19 …”
Section: Resultsmentioning
confidence: 99%
“…The two remaining studies included in our review were high quality placebo-controlled double-blind randomized trials of topical corticosteroids and vitamin D. 19 , 20 None of these treatments showed superiority compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though a moderate potency TCS was ineffective in a clinical trial for chronic chilblains, it is possible that the mechanism for chronic disease is different and that the moderate-potency TCS tested was not strong enough. 65 The second-line therapy for chilblains is a calcium channel blocker such as oral nifedipine: a double-blind, placebocontrolled trial found this drug to be efficacious for the treatment of chilblains. 66 The usual dosing is nifedipine 10 mg po TID with titration.…”
Section: Treatmentmentioning
confidence: 99%